2019
DOI: 10.21203/rs.2.12995/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between echocardiographic manifestations and bacterial species in patients with infective endocarditis: a cohort study

Abstract: Background The diagnosis of infective endocarditis (IE) is based on microbiological analyses and diagnostic imaging of cardiac manifestations. Echocardiography (ECHO) is preferred for visualization of IE-induced cardiac manifestations. We investigated correlations between bacterial infections and IE manifestations diagnosed by ECHO. Methods In this cohort study, data from patients aged 18 years or above, with definite IE admitted at the Karolinska University Hospital between 2008 and 2017 were obtained fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The cardiac clinical ICU showed a high consumption of oxacillin, which may be associated with the clinical picture of endocarditis and bacteremia caused by Staphylococcus aureus, one of the most prevalent pathogens found in this study. [24][25] It was observed that, in the cardiac surgical ICU, cefazolin was the most widely used antibiotic; the use of cefazolin in cardiac surgery is well documented in the literature, and may have contributed to the consumption found. [26][27] It is worth highlighting the consumption of the latest generation antimicrobial, ceftazidime/avibactam, indicated for the treatment of enterobacteria with multidrug-resistant KPC carbapenemases.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac clinical ICU showed a high consumption of oxacillin, which may be associated with the clinical picture of endocarditis and bacteremia caused by Staphylococcus aureus, one of the most prevalent pathogens found in this study. [24][25] It was observed that, in the cardiac surgical ICU, cefazolin was the most widely used antibiotic; the use of cefazolin in cardiac surgery is well documented in the literature, and may have contributed to the consumption found. [26][27] It is worth highlighting the consumption of the latest generation antimicrobial, ceftazidime/avibactam, indicated for the treatment of enterobacteria with multidrug-resistant KPC carbapenemases.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to the relatively high prevalence of patients with IDU among patients admitted to the hospital with IE, which was presented in a previous study [10]. According to guidelines, most of the patients with IE at the hospital are discussed within an endocarditis team, comprising specialists in infectious diseases, cardiology, clinical physiology and thoracic surgery [11].…”
Section: Study Settingmentioning
confidence: 99%
“…A clinical diagnosis of IE can be assisted utilizing the Duke Criteria, which determine the likelihood of IE based on clinical presentation and findings which are weighted by odds ratio; patients can be clinically diagnosed by meeting 2 major criteria, 5 minor criteria, or a combination of 1 major and 3 minor criteria-these criteria will be addressed in greater detail below. The best imaging modality for point-of-care diagnosis of IE is a transesophageal echocardiogram (TEE), though transthoracic echocardiography (TTE) may also identify advanced or severe disease [5]. Though imaging alone does not establish a definitive diagnosis of IE, it is important for clinicians to understand the high weight placed on echocardiographic findings (which fulfill one major Duke Criterion) and to be familiar with the imaging findings that should warrant further consideration of IE.…”
Section: Introductionmentioning
confidence: 99%